Nonthermal plasma-catalytic conversion of biogas to liquid chemicals with low coke formation. (1st July 2019) - Wang, Aiguo; Harrhy, Jonathan H.; Meng, Shijun; He, Peng; Liu, Lijia; Song, Hua
Graphical abstract: Nonthermal plasma-catalytic conversion of chemically inert and abundant greenhouse gases to high-value added liquid chemicals with limited coke formation under ambient condition. Highlights: Plasma-catalytic CH4 and CO2 co-conversion to liquid chemical is technically feasible. High liquid yield with low carbon formation is achieved over Pt/UZSM5 under plasma. Distribution of BAS and LAS is not a determining factor for the liquid chemical formation. Presence of weak acidic sites and Pt species benefit liquid formation with minimized coke. Abstract: Non-thermal plasma (NTP) assisted direct conversion of biogas (CH4 and CO2 ) into valuable liquid chemicals rather than syngas is investigated. The conversion of CH4 and CO2 is 22.1% and 16.2%, respectively, when combining NTP and Pt/UZSM5 catalyst. Approximately 60% yield of liquid products (formaldehyde, methanol, ethanol, and acetone) with limited carbon deposition (5.1%) is achieved. Coke formation is significantly lower than that has been previously reported in the dry reforming of methane with carbon dioxide to liquid oxygenate chemicals. High ratio of weak acidic sites and Pt species over zeolite catalyst benefit the formation of liquid chemicals and coke reduction, which can be used for catalyst modification to enhance the liquid yield and control coke formation.